2013
DOI: 10.1111/den.12164
|View full text |Cite
|
Sign up to set email alerts
|

Double staining with crystal violet and methylene blue is appropriate for colonic endocytoscopy: An in vivo prospective pilot study

Abstract: Background and AimEndocytoscopy (EC) at ultra-high magnification enables in vivo visualization of cellular atypia of gastrointestinal mucosae. Clear images are essential for precise diagnosis by EC. The aim of the present study was to evaluate the optimal staining method for EC in the colon.MethodsThirty prospectively enrolled patients were allocated 1:1:1 to three distinct staining methods: 0.05% crystal violet (CV) alone, 1% methylene blue (MB) alone, or CV + MB (CM double). Normal rectal mucosae were staine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…5). This may have been attributable to increased light intensity, increased exposure time of NBI, and improved noise reduction, thereby allowing clearer observation of the vessels and detailed examination of EC-V. With regard to advantages of EC-NBI over conventional EC, conventional EC always requires staining with crystal violet and methylene blue 16 17. However, EC-NBI does not require staining, and testing with EC-NBI therefore can be performed safely and quickly.…”
Section: Discussionmentioning
confidence: 99%
“…5). This may have been attributable to increased light intensity, increased exposure time of NBI, and improved noise reduction, thereby allowing clearer observation of the vessels and detailed examination of EC-V. With regard to advantages of EC-NBI over conventional EC, conventional EC always requires staining with crystal violet and methylene blue 16 17. However, EC-NBI does not require staining, and testing with EC-NBI therefore can be performed safely and quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in esophagus [46], stomach [47], and colon [48•] provide in vivo histology to identify histological characteristics. The combination of two contrast agents methylene blue and crystal violet allows for improved characterization of both epithelial structures and nuclei [49].…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…Recently, a new staining approach was introduced by Ichimasa and coworkers . The new approach consists of double staining containing crystal violet and methylene blue.…”
Section: Technique Of Endocytoscopymentioning
confidence: 99%
“…Those differences were calculated as statistically significant. It was therefore concluded that double staining with CV and MB, which rapidly provided recognizable images of both nuclei and gland formation, is an appropriate staining regimen for colonic endocytoscopic imaging …”
Section: Technique Of Endocytoscopymentioning
confidence: 99%